Thematic Village Program: The Problems of Changing Urban Village Spaces into Tourist Destinations - Rani Titis Sukowati (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2022)
The purpose of this article is to examine the change of urban kampung space into a tourist destination with the thematic kampung program. These changes were explored using the concepts of abstract space and Henri Lefebvre's social space which had not been used in the study of thematic kampung programs from previous literature studies. This article uses a qualitative approach with the type of case study research in three cities, namely Malang, Semarang, and Surakarta with the data source being digital paper. The results of the study of this article found that some thematic kampungs had not yet developed and might not be sustainable. Even though this program is expected to become a tourist destination, in reality there are still problematic thematic kampungs. The discontinuity of this thematic kampung refers to Lefebvre's concept of social space for residents where there are still residents who do not have awareness in developing their kampung, besides that the city government as an actor in abstract space in some cases still lacks support for kampung residents. So, if the city government wants to make thematic kampung a tourist destination, it is necessary to study each kampung further in seeing the potentials that exist in it, of course by combining ideas and concepts from residents.